IMPORT SUBSTITUTION: THE BOARDERS OF THE ENERGY SECURITY - N. N. Shvets (Vestnik MGIMO-Universiteta)
The article analyzes issues of import substitution in national production and determination of its effective scale considering the country's involvement to international division of labor and an important role of interstate cooperation in today's globalized world. The relevance of the study relies on the fact, that unfavorable global economic and politic situation in 2014-2015 raised concerns among the Russian authorities and the society in general about the stability of the economy and the necessity to increase its independence and self-sustainability. Sectoral economic sanctions imposed by western developed countries could potentially lead to disruptions in the supply of components and equipment that ensure the operation of power facilities. Currently power companies are influenced by the external economic situation and the devaluation of the national currency. As the result, goods of foreign manufacture have become significantly more expensive and opportunities for power companies to realize their investing and repair programs have been reduced. Thereby there is a high importance of developing the substitution-oriented production of the high-tech electric equipment within the Russian Federation's territory. Import substitution issues are closely related to the governmental industrial policy. The programs of the national production development need huge investments and that's why issues of economic effectiveness evaluation are highly relevant. But balances between economy's specialization and diversification, import substitution and export orientation are also highly important. Such measures directed at artificial import rationing as sanctions against foreign goods, creating favorable competitive environment for national producers, governmental grants could in prospect lead to a stagnation of the economy.